Who published what on Somali health issues? : Forming the policy for SHAJ through a bibliometric study - Bile, Khalif; Emmelin, Maria; Freij, Lennart; Gustafsson, Lars L; Sahlén, Klas-Göran; Wall, Stig; Warsame Yusuf, Marian (Somali Health Action Journal, 2022)
In this editorial we attempt to define additional rationales for SHAJ, the Somali Health Action Journal, further to those presented in our inaugural editorial. We recognize the health information divide as one of the three health gaps characterizing the global health inequality landscape. The SHAJ venture emerged from a joint Somali-Swedish initiative to revive a former collaborative research programme also recognizing the need for a Somali-based platform for research communication. The members of the SHAJ Editorial team decided to join forces in designing and carrying out an empirical bibliometric study to assess the state of the art of the published literature on Somali health issues over a 75-year period covering major societal development eras in Somali academic history. This editorial is basically presented in the form of a report from this study, concluding with a statement on the policy implications for SHAJ and Somali based research for health. The study raises concerns about the scarcity of research publications on Somali public health issues. This points to the need for research capacity strengthening in general and with special attention to the important role of the newly established Somali universities. We note a lack of balance regarding the topics and public health relevance of published papers in relation to the burden of prevailing health problems which calls for efforts to set research priorities in tune with the broad needs of the communities. Another observation is that the papers reviewed indicate a heavy dependence of the research agenda on external organisations and funders, which calls for active attention to research ownership issues in terms of Somali leadership and authorship. There is a lack of dissemination channels for Somali based health research and limited possibilities for young Somali scientists to publish their studies. As a Somali-owned journal, we envisage that SHAJ can play a catalytic role in the promotion and dissemination of "Essential Somali Health Research".